Indications for an EEG in a Child with ADHD - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators at Departments of Child Neurology, Neuroscience, Biostatistics, Marmara University, Istanbul, Turkey studied the parameters for prediction of epileptiform abnormalities in the EEG of 148 children diagnosed with ADHD, according to DSM-IV criteria, aged between 6 and 13 years (mean 8.76 +/- 1.26; 25.7% female).